Implementasi Metode Mind Mapping dalam Meningkatkan Hasil Belajar Siswa - Nunung Anidah (Peneliti.net, 2021)
This classroom action research aims to improve the learning outcomes of class VIII A students at MTs N 2 Pangandaran on business materials and simple planes in everyday life. Improving student learning outcomes by being given action through the Mind Mapping method. This research uses Classroom Action Research (PTK) or Classroom Action Research, which is a research activity carried out in class VIII A of the teaching and learning process using the mind mapping method which consists of several cycles. The population of this study were all students of class VIII A MTs N 2 Pangandaran with 27 students. The results of the study showed that student learning outcomes in learning business materials and simple aircraft in everyday life in class VIII A at MTs N 2 Pangandaran using the mind mapping method showed an increase from cycle to cycle. This can be seen with an increase in the average score from 61.4 in the pre-action to 75.8 in the first cycle or in other words, student learning outcomes increased 52%. Student learning outcomes in learning increased in cycle II with an increase in the average score to 83.3 or in other words an increase of 11% from cycle I. This proves that the learning process of business materials and simple aircraft in everyday life uses the method mind mapping can improve student learning outcomes